Acute alcoholic hepatitis and cellular Th1 immune responses to alcohol dehydrogenase. (26th February 2015) - Blackmore, Laura J; Ryan, Jennifer M; Huang, Xiaohong; Hussain, Munther; Triantafyllou, Evangelos; Vergis, Nikhil; Vijay, Godhev Manakkat; Antoniades, Charalambos G; Thursz, Mark R; Jassem, Wayel; Vergani, Diego; Shawcross, Debbie L; et al.
Abstract: Background: Alcoholic hepatitis is characterised by florid hepatic inflammation, liver failure, and death within 28 days in 35% of patients. We recently showed proliferative peripheral blood mononuclear cell (PBMC) responses to alcohol dehydrogenase (ADH) in patients with alcohol-related cirrhosis, associated with T-helper-type 1 (Th1) immunity and disease severity. We aimed to define whether ADH-specific cellular immunity is present in alcoholic hepatitis. Methods: PBMCs were collected from 15 patients with alcoholic hepatitis (modified Maddrey's discriminant function >32), nine with alcohol-related cirrhosis (long-term alcohol abstinence), and three healthy controls. 25 overlapping peptides, spanning the human ADH β1 subunit, were constructed. Proliferation to ADH peptides (1 × 10 5 cells per well, cultured with 10 mM peptides for 7 days) was assessed by 3 H-thymidine incorporation. A stimulation index (SI) of 2·5 or more was regarded as positive. ELISA measured concentrations of interferon γ (IFNγ), interleukin (IL) 17, and IL4 from supernatant. Findings: PBMCs from seven of 15 patients with alcoholic hepatitis recognised one to three ADH peptides (SI ≤5·7). IFNγ (mean 390·9 pg/mL [SE 31·4]) was detected in 48% of wells, IL17 (20·1 [3 ·4]) in 15%, and IL4 (90·5 [9·3]) in 14%. PBMCs from six of the nine patients with alcohol-related cirrhosis recognised one to five peptides (SI ≤5·2). IFNγ (360·7 [58·9], p>0·05) was detected in 31% of wells, IL17 (57·7 [10·9], p=0·0006) in 19%, and IL4 (219·7 [11·2], p=0·0012) in 28%. PBMCs from two healthy controls recognised one to two peptides (SI ≤3·1); all cytokine levels were below baseline. Interpretation: Proliferative anti-ADH immune responses in alcoholic hepatitis focused on individual epitopic regions. Predominance of proinflammatory Th1 responses was more pronounced in alcoholic hepatitis than in alcoholic-related cirrhosis. This finding requires investigation of targeted therapies to inhibit Th1 immunity in alcoholic hepatitis. Funding: Wellcome Trust.